2019
DOI: 10.1152/ajpheart.00088.2019
|View full text |Cite
|
Sign up to set email alerts
|

Direct CD137 costimulation of CD8 T cells promotes retention and innate-like function within nascent atherogenic foci

Abstract: Effector CD8 T cells infiltrate atherosclerotic lesions and are correlated with cardiovascular events, but the mechanisms regulating their recruitment and retention are not well understood. CD137 (4–1BB) is a costimulatory receptor induced on immune cells and expressed at sites of human atherosclerotic plaque. Genetic variants associated with decreased CD137 expression correlate with carotid-intimal thickness and its deficiency in animal models attenuates atherosclerosis. These effects have been attributed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Furthermore, CD8 T cells consistently associate with plaque development, so we chose to focus on them 20,21 . In the PCAL model, we observed a statistically significant 3-fold increase in CD8 T cells in the LCA under LDF, compared to the contralateral artery control, as we and others have reported previously 41,42 (Figure 4D&E). In ECKO mice, however, the expected increase of CD8 T cells in LDF vessels compared to contralateral normal laminar flow vessels did not occur (Figure 4D&E, P<0.01).…”
Section: Endothelium-specific Deletion Of Elavl1 Reduced Cd8 T Cells ...supporting
confidence: 87%
“…Furthermore, CD8 T cells consistently associate with plaque development, so we chose to focus on them 20,21 . In the PCAL model, we observed a statistically significant 3-fold increase in CD8 T cells in the LCA under LDF, compared to the contralateral artery control, as we and others have reported previously 41,42 (Figure 4D&E). In ECKO mice, however, the expected increase of CD8 T cells in LDF vessels compared to contralateral normal laminar flow vessels did not occur (Figure 4D&E, P<0.01).…”
Section: Endothelium-specific Deletion Of Elavl1 Reduced Cd8 T Cells ...supporting
confidence: 87%
“…These data suggested that CD8 ϩ T cells have a dual role in the post-MI wound healing process. Similar to what was observed in Xu et al (27), this study demonstrates a strong role of CD8 ϩ T cell-mediated action on monocyte/ macrophage recruitment and activation.…”
supporting
confidence: 90%
“…In human atherosclerotic plaques, the costimulatory receptor CD137 (4-1BB) was found to be expressed on activated T cells and to act in a TCR-independent manner [ 69 , 70 ]. This receptor belonging to the necrosis factor superfamily member serves as a costimulatory factor for T cells and drives T cell proliferation and cytokine production [ 69 , 71 ]. CD137 ligand (CD137L) is present on the cell surface of several APCs, including B cells, macrophages and dendritic cells, and increases in expression upon activation under chronic inflammatory conditions [ 70 ].…”
Section: Costimulation/-inhibition Of Cd8 + T Cmentioning
confidence: 99%
“…Treatment of Apoe −/− mice with a CD137 agonist caused increased T cell infiltration consisting mostly of CD8 + T cells, and elevated levels of proinflammatory cytokines [ 69 ]. Similarly, increased CD8 + T cell plaque infiltrates were seen in adoptive transfer experiments using wild type but not CD137-deficient CD8 + T cells specific for an unrelated antigen (ovalbumin) transferred into proprotein convertase subtilisin/kexin type 9 (PCSK9)-mediated hyperlipidemic mouse models upon ovalbumin immunization [ 71 ]. These lesional CD137 + effector CD8 + T cells promoted infiltration of endogenous CD8 + T cells with IFNγ-producing potential, whereas CD137-deficient CD8 + T cells exhibited impaired vessel infiltration, minimal IFN-γ production, and lead to also reduced infiltration of endogenous CD8 + T cells.…”
Section: Costimulation/-inhibition Of Cd8 + T Cmentioning
confidence: 99%